The Effects of Mindfulness Training on Emotion Regulation Among Undergraduates: A Randomized Controlled Trial - Feng, Yu; Wang, Xinling; Di, Bingbing; Wan, Feixue; Guo, Zhuoqi; Zhang, Hailong; Cheng, Liquan (Journal of Posthumanism, 2025)
This study investigated the effects of an 8-week mindfulness-based intervention on two key emotion regulation strategies—cognitive reappraisal and expressive suppression—among undergraduate students. It also examined whether post-intervention mindfulness level mediated the effects of the training. A randomized controlled trial (RCT) was conducted with 70 undergraduate students, randomly assigned to either a mindfulness training group or a waitlist control group. The intervention group participated in weekly 60-minute mindfulness sessions for eight weeks. Participants in the mindfulness group showed a significant increase in cognitive reappraisal and a decrease in expressive suppression, effects that were sustained at follow-up. Mediation analysis revealed that increases in mindfulness partially mediated the relationship between intervention and reappraisal. Mindfulness training is an effective intervention for improving emotion regulation in undergraduates. The findings highlight mindfulness as both an outcome and a mechanism of change, supporting its integration into university mental health and resilience programs.